Approaches of Assessing Understanding Using Video-Recall Data - Lazarov, Stefan Teodorov; Schaffer, Michael; Ronoh, Erick Kiprop

Entwicklung zukunftsfähiger Geschäftsmodelle in der Automatisierungstechnik anhand von Megatrends - Gräßler, Iris; Tusek, Alena Marie; Özcan, Deniz (Automation 2023)

IndQNER: Named Entity Recognition Benchmark Dataset from the Indonesian Translation of the Quran - Gusmita, Ria Hari; Firmansyah, Asep Fajar; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (Natural Language Processing and Information Systems)
Indonesian is classified as underrepresented in the Natural Language Processing (NLP) field, despite being the tenth most spoken language in the world with 198 million speakers. The paucity of datasets is recognized as the main reason for the slow advancements in NLP research for underrepresented languages. Significant attempts were made in 2020 to address this drawback for Indonesian. The Indonesian Natural Language Understanding (IndoNLU) benchmark was introduced alongside IndoBERT pre-trained language model. The second benchmark, Indonesian Language Evaluation Montage (IndoLEM), was presented in the same year. These benchmarks support several tasks, including Named Entity Recognition (NER). However, all NER datasets are in the public domain and do not contain domain-specific datasets. To alleviate this drawback, we introduce IndQNER, a manually annotated NER benchmark dataset in the religious domain that adheres to a meticulously designed annotation guideline. Since Indonesia has the world’s largest Muslim population, we build the dataset from the Indonesian translation of the Quran. The dataset includes 2475 named entities representing 18 different classes. To assess the annotation quality of IndQNER, we perform experiments with BiLSTM and CRF-based NER, as well as IndoBERT fine-tuning. The results reveal that the first model outperforms the second model achieving 0.98 F1 points. This outcome indicates that IndQNER may be an acceptable evaluation metric for Indonesian NER tasks in the aforementioned domain, widening the research’s domain range.
Keywords: NER benchmark dataset; Indonesian; specific domain

Lingua Franca – Entity-Aware Machine Translation Approach for Question Answering over Knowledge Graphs - Srivastava, Nikit; Perevalov, Aleksandr; Kuchelev, Denis; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille; Both, Andreas (Proceedings of the 12th Knowledge Capture Conference 2023)

The Power of Psalms in Post-Biblical Judaism. Liturgy, Ritual and Community

Europa erfahren, begreifen, vermitteln. Ansätze zur Entwicklung einer synkritischen Europadidaktik - Marchetti, Andreas; Schreckenberg, Stefan (Europa im Fremdsprachenunterricht Französisch, Italienisch & Spanisch. Sprachenpolitik, Kulturpluralität und Mehrsprachigkeit)

Write Your Song. Songwriting im Musikunterricht – ein Kartenspiel als Planungstool - Weidner, Verena; Hermann, Katharina; Godau, Marc (BMU Magazin)

Constructions de l'identité nationale - Tryptique identite-mémoire-nation. Le "grand débat sur l'identité nationale" - Karaca, Resul

Dysmas de Lassus: Verheissung und Verrat. Geistlicher Missbrauch in Orden und Gemeinschaften der katholischen Kirche. Münster 2022 - Priesching, Nicole (Theologische Revue)

Der Einfluss von kognitiver Belastung auf den Blicktäuschungseffekt im Basketball - Güldenpenning, Iris; Kunde, W.; Weigelt, Matthias (Human Performance – Assessment, Intervention & Analysen. Abstractband der 55. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Accelerating Concept Learning via Sampling - Baci, Alkid; Heindorf, Stefan (CIKM)

Characterization of Various Environmental Influences on the Inductive Localization - Lange, Sven; Hilleringmann, Ulrich; Hedayat, Christian; Kuhn, Harald; Förstner, Jens (2023 IEEE Conference on Antenna Measurements and Applications (CAMA))
In this paper, the influence of the environment on an inductive location system is analyzed. In the inductive location method, high frequency magnetic fields generated by planar coils lead to induction in other coils, which is used for localization analysis. Magnetic fields are not affected by changes in the dielectric properties of the environment, which is an advantage over other localization methods. However, electrical material parameters can still affect the localization results by indirect effects. For this reason, in this publication the influence will be investigated using real material parameters and their effects on the localization will be considered, so that the robustness and the limits of the inductive localization can be evaluated.
Keywords: Planar coils; inductive locating; magnetic fields; environmental influences; eddy currents; tet_topic_hf; tet_enas

A Memetic NSGA-II for the Multi-Objective Flexible Job Shop Scheduling Problem with Real-time Energy Tariffs - Burmeister, Sascha Christian; Guericke, Daniela; Schryen, Guido (Flexible Services and Manufacturing Journal)

Bring me my Meal on your Wheel - An Empirical Analysis of the Impact of Food Delivery Platforms on Local Restaurant Employment - Müller, Michelle; Neumann, Jürgen (Proceedings of the 56th Hawaii International Conference on System Sciences (HICSS))

Is it all about the setting? — A comparison of mathematical modelling with real objects and their representation - Jablonski, Simone (Educational Studies in Mathematics)
Abstract Mathematical modelling emphasizes the connection between mathematics and reality — still, tasks are often exclusively introduced inside the classroom. The paper examines the potential of different task settings for mathematical modelling with real objects: outdoors at the real object itself, with photographs and with a 3D model representation. It is the aim of the study to analyze how far the mathematical modelling steps of students solving the tasks differ in comparison to the settings and representations. In a qualitative study, 19 lower secondary school students worked on tasks of all three settings in a Latin square design. Their working processes in the settings are compared with a special focus on the modelling steps Simplifying and Structuring, as well as Mathematizing. The analysis by means of activity diagrams and a qualitative content analysis shows that both steps are particularly relevant when students work with real objects — independent from the three settings. Still, differences in the actual activities could be observed in the students’ discussion on the appropriateness of a model and in dealing with inaccuracies at the real object. In addition, the process of data collection shows different procedures depending on the setting which presents each of them as an enrichment for the acquisition of modelling skills.

Erzählen zu fantastischen Bildern. Kinder sprechen über Formen und Funktionen grammatischer Mittel in Erzählung - Drepper, Laura (Die Grundschulzeitschrift)

„Es gibt ja Zeichen für Wörter...". Grammatisches und Zeichenhaftes in Sprach(en)repertoires entdecken - Topalović, Elvira; Härtel, Kira (Die Grundschulzeitschrift)

GBP-Monitor: Betriebswirtschaftliche Einschätzungen und Erwartungen von Unternehmen in Deutschland. Unternehmenstrends im November 2023 - Maiterth, Ralf; Sureth-Sloane, Caren; Dyck, Daniel; Heinemann-Heile, Vanessa

The Cost of Tax Simplification: Evidence from Risk-taking in a Turnover-based Corporate Tax System - Amberger, Harald; Siahaan, Fernando; Sureth-Sloane, Caren

Umfrage: Beurteilung Investitionsfördernder Maßnahmen durch Unternehmen im Handwerk - Heinemann-Heile, Vanessa; Maiterth, Ralf; Sureth-Sloane, Caren